Diagnostics of the heliosphere by means of ground-based ULF observation - Saito,Takao; Yumoto,Kiyohumi; Tamura,Tadayoshi (1985)
P(論文) ULF waves have been utilized for diagnostics of the earth's magnetosphere since the 1960's. Similarly, an attempt is given in the present paper to diagnose the magnetosphere of the sun by utilizing the ULF waves observed at the Onagawa Magnetic Observatory. The diagnostics is based on the observed high correlation among the solar wind speed, amplitude and duration of Pc 3,which is the so-called sensitive anemometer for the solar wind. We selected the two extremes of distinct 27-day recurrence time patterns : the vertical pattern in 1974 and the horizontal pattern in 1954. From the vertical pattern, we diagnose the heliosphere with a tilted neutral sheet, which is the representative feature for the excursion phase of a solar cycle. While, the analysis of the horizontal pattern derives the heliosphere with a less-warped neutral sheet near the equatorial plane. This is the representative configuration of the heliomagnetospheric neutral sheet in the aligned phase. The two representative sheet configurations are discussed in terms of the solar cycle variation of the heliosphere. departmental bulletin paper